The Impact of FinTech on Profitability: An Analysis of Determinants in Banks of Middle East and North Africa (MENA) Region - Khalaf, Bashar Abu; Shaer, Abdulla Al- (International Journal of Membrane Science and Technology, 2023)
This study analyzed FinTech’s influence on MENA’s banking sector. This paper collected the data from Refinitiv Eikon platform and the bank’s annual reports, provided on the different Stock Exchanges websites. Our sample included Seven Countries namely; Qatar (7 Banks), United Arab Emirates (16 Banks), Kuwait (10 Banks), Egypt (10 Banks), Jordan (11 Banks), Saudi Arabia (10 Banks) and Turkey (9 Banks). Specifically, 73 Banks in the MENA region has been collected during the period 2014-2021 to investigate the impact of Fintech on Banks profitability. The model developed included several independent variables, such as the number of ATM machines, internet banking, size, growth and mobile application’s availability, while the dependent variable is profitability (Return on Assets). The model used was estimated using panel regression (fixed and random effect techniques), Hausman test favored the fixed effect results. The results indicated that the number of ATM machines affects the bank’s performance negatively. This suggests that the higher the number of ATM machines, the lower the performance, since the higher cost related to the usage of such machines with no charge of usage. However, internet banking, mobile applications and size affect Return on Assets positively.